Direct Observation of Simultaneous Immobilization of Cadmium and Arsenate at the Brushite-Fluid Interface - Zhai, H.; Wang, L.; Qin, L.; Zhang, W.; Putnis, Christine; Putnis, Andrew (American Chemical Society, 2018)
Cadmium (Cd 2+ ) and Arsenate (As 5+ ) are the main toxic elements in soil environments and are easily taken up by plants. Unraveling the kinetics of the adsorption and subsequent precipitation/immobilization on mineral surfaces is of considerable importance for predicting the fate of these dissolved species in soils. Here we used in situ atomic force microscopy (AFM) to image the dissolution on the (010) face of brushite (dicalcium phosphate dihydrate, CaHPO 4 Â·2H 2 O) in CdCl 2 - or Na 2 HAsO 4 -bearing solutions over a broad pH and concentration range. During the initial dissolution processes, we observed that Cd or As adsorbed on step edges to modify the morphology of etch pits from the normal triangular shape to a four-sided trapezium. Following extended reaction times, the respective precipitates were formed on brushite through a coupled dissolution-precipitation mechanism. In the presence of both CdCl 2 and Na 2 HAsO 4 in reaction solutions at pH 8.0, high-resolution transmission electron microscopy (HRTEM) showed a coexistence of both amorphous and crystalline phases, i.e., a mixed precipitate of amorphous and crystalline Cd (5-x) Ca x (AsO 4 ) (3-y) (PO 4 ) y OH phases was detected. These direct dynamic observations of the transformation of adsorbed species to surface precipitates may improve the mechanistic understanding of the calcium phosphate mineral interface-induced simultaneous immobilization of both Cd and As and subsequent sequestration in diverse soils.